(3OjhGf CSGeI Hf efbPs - (3GSGeI Hf efbP , GSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHj, CHh GdeXaQ,J (B584 (3g` s
(3ChdgG (B:s
(3CbGdc Gddg UabI GdfOe hCadc ef PdI GdbOe hCYdGc ef NW GdebGd hCLQGMg hMUGjO s
(3BNQgG (B:s
(3hBNQ GdehLhO efg hbGd HMeU jG bdH QabkG HeG ef LdOi ce PG GdMfjf Edi ef CfJ eKhGg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B282s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs